Geographic encoding of transcripts enabled high-accuracy and isoform-aware deep learning of RNA methylation. Issue 18 (26th September 2022) - Huang, Daiyun; Chen, Kunqi; Song, Bowen; Wei, Zhen; Su, Jionglong; Coenen, Frans; de Magalhães, João Pedro; Rigden, Daniel J; Meng, Jia
Abstract: As the most pervasive epigenetic mark present on mRNA and lncRNA, N 6 -methyladenosine (m 6 A) RNA methylation regulates all stages of RNA life in various biological processes and disease mechanisms. Computational methods for deciphering RNA modification have achieved great success in recent years; nevertheless, their potential remains underexploited. One reason for this is that existing models usually consider only the sequence of transcripts, ignoring the various regions (or geography) of transcripts such as 3′UTR and intron, where the epigenetic mark forms and functions. Here, we developed three simple yet powerful encoding schemes for transcripts to capture the submolecular geographic information of RNA, which is largely independent from sequences. We show that m 6 A prediction models based on geographic information alone can achieve comparable performances to classic sequence-based methods. Importantly, geographic information substantially enhances the accuracy of sequence-based models, enables isoform- and tissue-specific prediction of m 6 A sites, and improves m 6 A signal detection from direct RNA sequencing data. The geographic encoding schemes we developed have exhibited strong interpretability, and are applicable to not only m 6 A but also N 1 -methyladenosine (m 1 A), and can serve as a general and effective complement to the widely used sequence encoding schemes in deep learning applications concerning RNA transcripts.